2007
DOI: 10.1024/0036-7281.149.12.559
|View full text |Cite
|
Sign up to set email alerts
|

Herniation of the urinary bladder through a congenitally enlarged inguinal canal in a cat

Abstract: A two-year-old, castrated male Main Coon cat was referred because of chronic, recurrent pollakiuria, haematuria, and acute vomiting. On clinical examination, a smooth, soft-tissue mass, suspected to be the urinary bladder, was palpable outside of the abdominal wall in the inguinal area. On radiographs, the urinary bladder was found to be extra-abdominal, and herniated through an enlarged right inguinal canal at exploratory coeliotomy. The left inguinal canal was also enlarged. The urinary bladder was repositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In horses, the most common organ involved in inguinal herniation is the small intestine (Schumacher 2006). To our knowledge, herniation of the urinary bladder has not been reported in horses, although it has been reported in cats (Zulauf et al. 2007), dogs (Bellenger 1996) and man (Curr et al.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In horses, the most common organ involved in inguinal herniation is the small intestine (Schumacher 2006). To our knowledge, herniation of the urinary bladder has not been reported in horses, although it has been reported in cats (Zulauf et al. 2007), dogs (Bellenger 1996) and man (Curr et al.…”
Section: Discussionmentioning
confidence: 86%
“…Urinary catheterisation confirmed that the mass in the inguinal region was the bladder however other diagnostic techniques have proved useful in other species. Air contrast radiography has been used to confirm bladder involvement in an inguinal hernia in a cat (Zulauf et al. 2007) but we believe that even in a foal this technique would prove difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Clinical signs included chronic lower urinary tract signs, and a soft mass was palpated in the region. Radiography revealed the urinary bladder to be extraabdominal.…”
Section: Urinary Bladder Herniationmentioning
confidence: 99%
“…Blunt trauma has been reported to be the most common cause of traumatic herniation in dogs and cats (Kraus, 1990;Shaw et al, 2003). Perineal and inguinal herniation of the urinary bladder both occur in the cat (Risselada et al, 2003;Zulauf et al, 2007). Rupture of an umbilical hernia and subsequent bladder herniation have also been reported in humans (Pandey et al, 2008).…”
Section: Introductionmentioning
confidence: 96%